The Adventures of John Jewitt : Only Survivor of the Crew of the Ship Boston During a Captivity of Nearly Three Years Among the Indians of Nootka Sound in Vancouver Island - Jewitt, John Rodgers, 1783-1821; Brown, Robert, 1842-1895 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Adventures of John Jewitt" by John Rodgers Jewitt is a historical account written in the early 19th century. The book narrates the gripping tale of John Jewitt, who was the only survivor of the crew of the ship Boston following its capture by the Nootka Indians in Canada. Drawing on his experiences during nearly three years of captivity, Jewitt chronicles his interactions with the indigenous tribes, the threats they posed, and his eventual escape. The opening of the narrative introduces Jewitt's journey, beginning with his background in England and his decision to sail to America aboard the Boston. Upon entering Nootka Sound, Jewitt and his crew encounter the local inhabitants and engage in trade, unaware of the violent turn their fate will take. Tensions arise quickly, and after a series of miscommunications and unintentional insults, Jewitt witnesses the brutal massacre of his crewmates as the Nootka people take control of the ship. This shocking event sets the stage for Jewitt's survival and later reflections on the complexities of his captors and the harsh realities of his situation. (This is an automatically generated summary.)
Release date is 2011-11-14
E-text prepared by Moti Ben-Ari and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://www.archive.org)
Keywords: Indian captivities; Nootka Indians; Nootka Sound (B.C.)